Computer Assisted Cartography in Nautical Charting — An Appraisal - Satyanarayana, Shri P.; Prakash, Satya (The International Hydrographic Review, 2015)
Computer Assisted Cartography (CAC) is the application of modern computer technology in the fields of data capturing, processing and production. CAC has played a prominent role in i) acquisition of data through Automatic Data Logging Systems (ADLS), ii) creation of Data Bases of map/chart files using manual/automatic digitizers, Hi) editing of data by Interactive Graphic Terminals (GRT), iv) precise plotting and projection of data using sophisticated plotters, v) scribing of lineal details/symbols, vi) photoflashing and photo plotting of alphanumeric details/symbols on film , vii) preparation of colour separation/ribbon originals. Thus CAC has taken over almost all roles of the time consuming conventional/manual cartography of hand print, stick up of phototyped alphanumeric details/symbols, hand scribe and manual colour separation. CAC has radically reduced the time span of chart making and provides fast, accurate and uniform results. A computer assisted, cartographic plotting system consisting of an on-line system for data base generation and an off-line precision plotting system for preparation of fair drawing originals was installed in the Naval Hydrographic Office (NHO), Dehra Dun in 1981. The paper outlines the process of chart production by CAC and discusses the functions of different units of the system such as the digitizer, verification plotter, graphic terminal, precision plotter, etc. The authors have made an appraisal of the functioning of CÀC in nautical charting in NHO during the past 5 years and have explained various problems/setbacks that were encountered by cartographic programmers and draughtsmen in running the auto chart system and how these were overcome by continued Research and Development (R&D) efforts. The paper reveals that initially compilations were not computer compatible, which resulted in positional errors/shift in plots, misinterpretation and misrepresentation. Standards for preparing computer compatible compilations have now been laid down. The ‘cartographic rigidity’ based on technical principles initially provoked resistance from certain cartographers and draughtsmen in accepting the CAC product. However, CAC products are now being accepted with minor reservations as these are drawn in a clear, sharper, uniform, accurate and faster manner. The authors are of the opinion that nautical cartographers and draughtsmen who have the knowledge of charting practices and navigational requirements are better suited for working on the system than those persons without this specialized knowledge. The paper outlines the R&D efforts and discusses various modifications made in original software and how certain new software was developed for projection, lattices, etc. The CAC in NHO is being maintained in-house by qualified electronic engineers. However, due to non availability of certain spares indigeneously the system at times becomes non-operational. The authors have pointed out the limitation of new technology and have outlined the compromises that have been made. There are still certain unsolved problems in text depiction, positioning of finely curved details, overlapping of details at sharp turns, plotting breakers, rotation of specific symbols, etc. However, it is felt that despite certain reservations CAC will continue to function as a useful tool for data storage, chart revision and production. It will also play a significant role in development of the new technique of the ‘electronic chart’.